Capoeira and scenography: possible dialogues through space (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Based on questions raised by the analysis of a typical Brazilian cultural manifestation, capoeira, some conceptual operators are listed in order to understand how the scenic space is currently characterized. It was taken as a hypothesis that the contemporary performance design seeks to investigate several ways that define the relationship between action and reception, which directly influence the creation of scenic spatiality. This paradigm shift, which is evidenced with the help of capoeira analysis, affects the very idea of scenography: this becomes a spatial practice that is currently practiced in order to catalyze flows and encode the bodies and movements of those who involve in the scenic event.
Keywords: Scenography; Spatial configuration; Capoeira; Performance; Design